THE ISSUE OF TRANSPORT DOCUMENTS IN SHIPPING - Matura, Ladislav; Sosedova, Jarmila; Slesinger, Jan (Doprava a spoje, 2009)
Article discusses the importance of the conclusion of the maritime transport of cargo and highlights the role of this legal document in relation to the carrier. Examples are given associated forms of these contracts, which are different degree of responsibility for the carriage of cargo and provide a forum for fraudulent activity. They are practical comments on the new rules introduced in this issue towards their formal simplicity.